Development of A Framework for an Asynchronous Discussion Forum through an E-Learning Platform - Durairaj, Kamalambal; bin Assarnurkutty, Shah Jahan; Thoe, Ng Khar; Mohd Sabri, Wan Noor Adzmin bt (Universitas Muhammadiyah Purwokerto, 2022)
Throughout the last several decades, the digital era has expanded the process of information sharing in classroom instruction in novel and surprising ways with reference to a wide variety of complex challenges. As a result, effective interactive e-learning management is critical for removing barriers to